River animals - Galko, Francine (Chicago : Heinemann Library, 2003)
Explores the animals that make their habitat in rivers and streams.
Includes bibliographical references (p. 31) and index.
3.8
K-3
Keywords: Stream animals -- Juvenile literature; Rivers -- Juvenile literature; Stream animals; Rivers; Stream animals; Rivers; Animals -- Rivers and streams; Stream ecology; Animals -- Habitat; Aquatic animals